Suite-based Monitoring Model to Control the Distance Learning Quality During the Covid-19 Pandemic - Ari Pujianto; Bambang Ismanto; Wahyudi (Jurnal Ilmiah Sekolah Dasar, 2022)
The monitoring of the education quality standards on the implementasion of the distance learning during the Covid-19 pandemic had proven to be difficult. This study aims to develop a monitoring model by utilizing the Gsuite facility to assist principals in supervising learning activities carried out by teachers. This development research used the Borg and Gall model which had been adapted by Lawrence Cunningham. FGD (Focus Group Discussion) and SWOT analysis were used during the research, starting from collecting information, setting goals, making initial models, testing, and evaluating until the final model was produced. The trial was carried out by involving 20 respondents consisting of principals and teachers. The results of the trial and application of the model showed significant results. MMBGSuite's product have met the standard eligibility criteria by showing results of 82.9% for media validation and 76.2% for content or material validation so that it declare to get the “feasible” predicate. Likewise for practicality standards, MMBGSuite also received a percentage score of 80.6% from teachers and 85.4% from school principals indicating that this model is easy to use and practical. The results of this study indicate that the Gsuite-based monitoring model (MMBGSuite) can provide solutions to facilitate school principals in carrying out supervision and controlling the quality of the academic activities when distance learning was implemented during the Covid-19 pandemic.